Association of low maternal levels of salusins with gestational diabetes mellitus and with small-for-gestational-age fetuses - Celik, Ebru; Celik, Onder; Yilmaz, Ercan; Turkcuoglu, Ilgin; Karaer, Abdullah; Turhan, Ugur; Aydin, Suleyman (Elsevier, 2013)
Objectives: To evaluate maternal and cord serum concentrations of salusin-alpha and salusin-beta in women with gestational diabetes mellitus (GDM) and with small-for-gestational age (SGA) fetuses. Study design: Pregnant women with GDM (n = 25), women with SGA (n = 20) and maternal age-matched normal healthy pregnant subjects (n = 25) participated in the study. Maternal serum and cord blood salusin-alpha and salusin-beta levels at the time of birth were measured using ELISA, and their relation with metabolic parameters was also assessed. Results: Mean concentrations of maternal and fetal serum salusin-alpha in the GDM and SGA groups were significantly lower than those of the controls (P < 0.001, P < 0.001, P < 0.001 and P < 0.001, respectively). Mean concentrations of maternal and cord blood salusin-beta also decreased in both the GDM and the SGA groups in comparison to the control group (P < 0.001, P < 0.001, P < 0.001 and P < 0.001, respectively). The concentrations of maternal serum salusin-alpha and salusin-beta were strongly positively correlated with the concentrations of cord blood salusin-alpha and salusin-beta (R = 0.92, P < 0.001 and R = 0.94, P < 0.001, respectively). Conclusions: The low levels of maternal serum salusin-alpha and salusin-beta may have negative impact on metabolic disorders and vascular dysfunction. (C) 2012 Elsevier Ireland Ltd. All rights reserved.
Keywords: Gestational diabetes mellitus; Small-for-gestational age; Cord blood; Salusin-alpha; Salusin-beta; HOMA-IR